ICT-induced Technological Progress and Employment: a Happy Marriage or a Dangerous Liaison? A Literature Review - Anna Sabadash (European Commission, Joint Research Centre (JRC), 2013)
This report surveys the literature on the employment impact of ICT. Two competing views - compensation and substitution theory - dominate the current economic debate. The first assumes that the labour-saving impact of technological progress is counterbalanced by various compensation mechanisms. The second asserts that technology cause job displacement, leading to polarization, de-skilling and possibly a jobless economy. Recent employment trends are often seen as indicative of mismatches between rapidly changing demand for skills and slow adjustment in the supply. Despite a wealth of theoretical models and empirical evidence, a consensus regarding the employment effect of ICT remains elusive. While there are many empirical studies on technological progress in general, few are based on specific ICT indicators. Our review devotes equal space to each mainstream economic theory on the complex connection between technology and employment, while giving greater emphasis to those studies which specifically look at ICT and that provide empirical support to sound theoretical grounds. This report recommends further empirical research on the specific employment impact of ICT.
Keywords: E24; J21; J23; O33; 330; ICT; technological progress; innovation; employment; skills; occupations